Causes of incontinence in the elderly - Samalavičiūtė, Ieva Marija; Tarasevič, Diana; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
The article analyzes the causes of incontinence, which affect the quality of life of men and women and are often related to the phenomenon of aging. Objective. To examine the causes of urinary incontinence among elderly based on the results of the scientific literature. Research methods. Data was collected in: Am J Obstet Gynecol, Clin Geriatric Med, Am J of nursing, BMC, PubMed database. Full-text articles on urinary incontinence were used for the analysis, when their title, keywords: incontinence, cause of urinary incontinence, elderly people, lack of knowledge about urinary incontinence (incontinenza urinaria) met the purpose of the review. Only publications in English, which were published in the period 2017–2022, were analyzed 27 scientific papers on the subject are included and analyzed in the systematic review. Research results and conclusions. The results showed that incontinence is associated with age, overweight, chronic diseases, bad habits, post-menopausal hormone replacement therapy. Incontinence increases social isolation, anxiety, and depression. Non-invasive methods are used to eliminate the causes of incontinence: psychological training, giving up bad habits, promoting a healthy and balanced diet, regulating body weight. Botulinum toxin injections, urological surgery or sacral nerve stimulation are used to enhance the treatment effect. The knowledge of patients and medical staff about the urinary incontinence is fundamental.